Acceptance of virtual consultations among older adults and caregivers in Malaysia: a pilot study during the COVID-19 pandemic. Issue 2 (17th February 2022) - Tan, Yi Ru; Tan, Maw Pin; Khor, Mei Mei; Hoh, Hon Bing; Saedon, Nor'Izzati; Hasmukharay, Kejal; Tan, Kit Mun; Chin, Ai Vyrn; Kamaruzzaman, Shahrul B; Ong, Terence; Davey, Gareth; Khor, Hui Min
ABSTRACT: Aim: The COVID-19 pandemic has disrupted the delivery of healthcare to vulnerable older adults, prompting the expansion of telemedicine usage. This study surveyed the acceptance of virtual medical consultations among older adults and caregivers within geriatric outpatient services in a tertiary hospital during the pandemic. Methods: A cross-sectional survey was conducted among caregivers and patients attending geriatric outpatient services in Kuala Lumpur, Malaysia. The survey measured the availability of equipment for virtual consultations, prior knowledge and experience of telemedicine, and willingness to consult geriatricians through virtual technology, using the Unified Theory of Acceptance and Use of Technology (UTAUT) scale. Results: A total of 197 caregivers and 42 older patients with a mean age of 54.28 (±13.22) and 75.62 (±7.32) years, respectively, completed the survey. One hundred and fifty-six (79.2%) of the caregivers were adult children accompanying patients. The mean UTAUT score was 65.97 (±13.71) out of 90, with 66.64 (±13.25) for caregivers and 62.79 (±15.44) for older adults, suggesting a high acceptance of adopting virtual consultations in lieu of face-to-face care. The independent predictors of acceptance of virtual consultation were : possession of an electronic device capable of video-communication, living with someone, living in a care home, weekly online banking usage, and perceived familiarity with virtual platforms. Conclusion: Caregivers and patients indicated a high level of acceptance of virtual medical consultations, which is likely facilitated by caregivers such as adult children or spouses at home or staff in care homes. To minimize the transmission of COVID-19 in a highly vulnerable group, virtual consultations are an acceptable alternative to face-to-face consultations for older people and their caregivers in our setting.